2017
DOI: 10.1111/sjop.12369
|View full text |Cite
|
Sign up to set email alerts
|

Using the regulation of accuracy to study performance when the correct answer is not known

Abstract: We examined memory performance in multiple-choice questions when correct answers were not always present. How do participants answer when they are aware that the correct alternative may not be present? To answer this question we allowed participants to decide on the number of alternatives in their final answer (the plurality option), and whether they wanted to report or withhold their answer (report option). We also studied the memory benefits when both the plurality and the report options were available. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In relation to the type of answer requested, we implemented in one step (see Figure 1) the combination of the plurality option (Luna, et al, 2011) along with the report option (Koriat & Goldsmith, 1994), and only the eye-tracking measures during the selection of these combined answers were the object of our analysis. Both plurality and report options are procedures used to study the informativeness-accuracy trade-off in memory reporting (Luna & Martín-Luengo, 2017;Martín-Luengo et al, 2018;Martín-Luengo et al, 2021). In case of the plurality option, participants are first requested to select or provide one candidate answer (i.e., single answer) and then to add more alternatives conforming to the plural answer.…”
Section: The Present Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the type of answer requested, we implemented in one step (see Figure 1) the combination of the plurality option (Luna, et al, 2011) along with the report option (Koriat & Goldsmith, 1994), and only the eye-tracking measures during the selection of these combined answers were the object of our analysis. Both plurality and report options are procedures used to study the informativeness-accuracy trade-off in memory reporting (Luna & Martín-Luengo, 2017;Martín-Luengo et al, 2018;Martín-Luengo et al, 2021). In case of the plurality option, participants are first requested to select or provide one candidate answer (i.e., single answer) and then to add more alternatives conforming to the plural answer.…”
Section: The Present Researchmentioning
confidence: 99%
“…Therefore, we decided to combine them in order to offer participants the widest possible (but still fully controlled in counterbalanced fashion) set of answer alternatives: single report, single withhold, plural report, plural withhold. This is not the first experiment where plurality and report options are used at in one experiment (Luna & Martín-Luengo, 2017;Martín-Luengo et al, 2018), but this is the first time both tasks are used in a single step. Despite this methodological alteration, we do not expect to find any major difference in the distribution of the answers among the four options.…”
Section: The Present Researchmentioning
confidence: 99%
“…Otherwise, it is withheld.1 1 If the criteria are not met, then the information can also be modified and a new comparison against criteria is made. There are several modifications that can be made depending on the nature of the information (see for example, Luna and Martín-Luengo, 2017; see also Goldsmith, 2016, for a review), but here we will focus in the report option and the decision to report or withhold an answer.…”
Section: Tailoring a Message: The Report Optionmentioning
confidence: 99%
“…The regulation of accuracy refers to people's ability to modify or alter some dimensions of their discourse to maximize their accuracy (Luna & Martín‐Luengo, ). For example, a witness may think that she is not certain enough about a given piece of information and, thus, may decide not to report it (i.e., the report option, Higham, Luna, & Bloomfield, ).…”
mentioning
confidence: 99%
“…In the typical version of the procedure, participants are requested to (a) select one alternative (specific answer), (b) select three alternatives (generic answer), and (c) select which answer, specific or generic, they would prefer to provide were they in court. Research has shown that allowing participants to decide the number of alternatives in their response increases the accuracy of their final report, not only in eyewitness settings (Luna et al, , ; Luna & Martín‐Luengo, , , ), but also in educational contexts (Higham, ), and in conversational exchanges (Martín‐Luengo, Shtyrov, Luna, & Myachykov, ).…”
mentioning
confidence: 99%